Virtual reality gaming : perspectives on immersion, embodiment and presence - Evans, Leighton (Emerald Publishing Limited, 2025)
This volume contains an Open Access Chapter Offering a comprehensive and research-oriented survey of the emergence of virtual reality (VR) into the gaming mainstream, Virtual Reality Gaming delves into the complexities of VR gaming, emphasising immersion, embodiment, and player presence. As the first study to critically assess and systematically investigate the phenomenon of VR Gaming through the tripartite lens of embodiment, presence, and immersion, established and emerging voices in the field discuss the unique aspects of VR games and the challenges they present to researchers and designers with regards to re-conceptualising the relationship between system, player and game play - in essence, a reconsideration of the human-computer interface (HCI) of gaming. Each chapter develops the existing scholarship on all these areas, creating a discourse on each element of embodiment, presence, and immersion that will improve the understanding of all these concepts in the context of gaming and VR. A major contribution to the fields of gaming, HCI, VR and media studies, Virtual Reality Gaming is of interest not only to scholars, students and academics researching within this area, but also to practitioners and professionals in the gaming industry.
Includes index.
Keywords: Video games -- Psychological aspects.; Virtual reality.; Games & Activities -- Video & Mobile.; Computer and video game industry.; Computer games, online games: strategy guides.; elektronické knihy; electronic books